Uji Toksisitas Subkronik Jamu Asam Urat pada Hati Mencit Galur Balb-C (Subchronic Toxicity Study of Jamu Asam Urat in Liver of Balb-C Mice) - M Nuril Huda; Diana Holidah; Fifteen Aprila Fajrin (Pustaka Kesehatan, 2017)
Jamu asam urat is one of the most-consumed herbal medicine product to threat gout arthritis. This study aimed to determine of jamu asam urat effect for long-term consumption on mice's liver. Mice were divided into 4 groups of 10 each group. A control group was administered with aquadest and 3 treatment groups were administered with jamu sample per oral in dose of 1,800 (D1); 3,600 (D2); and 7,200 mg/kg BW (D3) in 28 days. The examination included GPT and GOT serum level measurement and liver histopathology. The result showed that GPT serum level was 34.33 ± 2.48 U/L (D1), 41.20 ± 1.94 U/L (D2), and 46.32 ± 2.84 U/L (D3), while GOT serum was 44.60 ± 2.94 U/L (D1), 55.53 ± 3.22 U/L (D2), and 63.31 ± 2.63 U/L (D3), respectively. Parenchymatous degeneration and necrosis in liver were found in histopathology examination. Increase of GPT, GOT level, and parenchymatous degeneration liver changes at D1 and D2 counted as mild degeneration, meanwhile necrosis change at D3 counted as moderate degeneration but it did'nt greatly affect liver function. Thus jamu asam urat is still save to be consumed. Keywords: subchronic toxicity, jamu asam urat, GPT, GOT, liver histopathology